Microbial Biomarker Transition in High-Altitude Sinter Mounds From El Tatio (Chile) Through Different Stages of Hydrothermal Activity - Sanchez-Garcia, Laura; Fernandez-Martinez, Miguel Angel; García-Villadangos, Miriam; Blanco, Yolanda; Cady, Sherry L.; Hinman, Nancy; Bowden, Mark E.; Pointing, Stephen B.; Lee, Kevin C.; Warren-Rhodes, Kimberly; Lacap-Bugler, Donnabella; Cabrol, Nathalie A.; et al. (Frontiers in Microbiology, 2019)
Geothermal springs support microbial communities at elevated temperatures in an ecosystem with high preservation potential that makes them interesting analogues for early evolution of the biogeosphere. The El Tatio geysers field in the Atacama Desert has astrobiological relevance due to the unique occurrence of geothermal features with steep hydrothermal gradients in an otherwise high altitude, hyper-arid environment. We present here results of our multidisciplinary field and molecular study of biogeochemical evidence for habitability and preservation in silica sinter at El Tatio. We sampled three morphologically similar geyser mounds characterized by differences in water activity (i.e. episodic liquid water, steam, and inactive geyser lacking hydrothermal activity). Multiple approaches were employed to determine (past and present) biological signatures and dominant metabolism. Lipid biomarkers indicated relative abundance of thermophiles (dicarboxylic acids) and sulfate reducing bacteria (branched carboxylic acids) in the sinter collected from the liquid water mound; photosynthetic microorganisms such as cyanobacteria (alkanes and isoprenoids) in the steam sinter mound; and archaea (squalane and crocetane) as well as purple sulfur bacteria (cyclopropyl acids) in the dry sinter from the inactive geyser. The three sinter structures preserved biosignatures representative of primary (thermophilic) and secondary (including endoliths and environmental contaminants) microbial communities. Sequencing of environmental 16S rRNA genes and immuno-assays generally corroborated the lipid-based microbial identification. The multiplex immunoassays and the compound-specific isotopic analysis of carboxylic acids, alkanols, and alkanes indicated that the principal microbial pathway for carbon fixation in the three sinter mounds was through the Calvin cycle, with a relative larger contribution of the reductive acetyl-CoA pathway in the dry system. Other inferred metabolic traits varied from the liquid mound (iron and sulfur chemistry), to the steam mound (nitrogen cycle), to the dry mound (perchlorate reduction). The combined results revealed different stages of colonization that reflect differences in the lifetime of the mounds, where primary communities dominated the biosignatures preserved in sinters from the still active geysers (liquid and steam mounds), in contrast to the surviving metabolisms and microbial communities at the end of lifetime of the inactive geothermal mound.